In situ label-free monitoring of human adipose-derived mesenchymal stem cell differentiation into multiple lineages. (February 2018) - Suhito, Intan Rosalina; Han, Yoojoong; Min, Junhong; Son, Hyungbin; Kim, Tae-Hyung
Abstract: Precise characterizations of stem cell differentiation into specific lineages, especially in non-destructive and non-invasive manner, are extremely important for generating patient-specific cells without mass loss of differentiated cells. Here, we report a new method capable of in situ label-free quantification of stem cell differentiation into multiple lineages, even at a single cell level. The human adipose-derived mesenchymal stem cells (hADMSCs) were first differentiated into two different types of cells (osteoblasts and adipocytes) and these differentiated cells were then intensively analyzed by micro-Raman spectroscopy. Interestingly, the Raman peaks assigned to lipid droplets and hydroxyapatite were found to be highly specific to the adipocyte (fat cell) and osteoblast (bone cell) and were thus found to be useful for generating label-free single cell Raman images in combination with CH3 (2935 cm −1 ) peaks for visualizing cell shape. Remarkably, based on these Raman images, we found that the osteogenesis of hADMSCs could be determined and quantified after 9 days of differentiation, which is a week earlier than with the typical alizarin red staining method. In the case of adipogenesis, the increase of lipid droplets in the cytoplasm at the single cell level could be clearly visualized and detected during the entire period of adipogenesis, which is impossible using any other currently available methods such as Oil Red O and immunostaining. Hence, the new method reported in this study is highly promising as an analytical tool for precise in-situ monitoring of stem cell differentiation, and could facilitate the use of stem cell-based materials for the regenerative therapies.